Understanding the origin of phase segregation of nano-crystalline in a BexZn1−xO random alloy: a novel phase of Be1/3Zn2/3O. Issue 21 (7th June 2015) - Yong, Dingyu; He, Haiyan; Su, Longxing; Zhu, Yuan; Tang, Zikang; Zeng, Xiao Cheng; Pan, Bicai
<x xml:space="preserve">Abstract</x> The usage of a BexZn1−xO alloy in ultraviolet (UV)-region optoelectronic devices is largely hindered by its intricate phase segregation of crystallites of different sizes.